A Titanium‐Catalyzed Reductive α‐Desulfonylation. Issue 20 (5th March 2021) - Kern, Christoph; Selau, Jan; Streuff, Jan
Abstract: A titanium(III)‐catalyzed desulfonylation gives access to functionalized alkyl nitrile building blocks from α‐sulfonyl nitriles, circumventing traditional base‐mediated α‐alkylation conditions and strong single electron donors. The reaction tolerates numerous functional groups including free alcohols, esters, amides, and it can be applied also to the α‐desulfonylation of ketones. In addition, a one‐pot desulfonylative alkylation is demonstrated. Preliminary mechanistic studies indicate a catalyst‐dependent mechanism involving a homolytic C−S cleavage. Abstract : Catalyst‐controlled cleavage : A transition‐metal‐catalyzed desulfonylation gives access to functionalized nitriles and ketones from readily‐available α‐sulfonylated precursors. The homolytic reductive C−S cleavage occurs under the control of an in situ generated titanium(III) catalyst and it can be combined with a Michael addition reaction to achieve a one‐pot desulfonylative alkylation.